TEKNOLOGI INFORMASI UNTUK KEUNGGULAN STRATEGIS: KONSEP DAN MODEL - Ronowati Tjandra (Akademi Akuntansi YKPN Yogyakarta, 2009)
Lately, information technology (IT) is used to produce efficiency and effectiveness, and to win the battle. In other words, information technology (IT) is an effective weapon in economic competition so that the companies’ goal. The discussion of information technology involves information as paper dragon goal supporter, management control, strategic source, strategic tool and competitive advantage. Strategic information technology differs from conventional information technology in terms of orientation, goal, focus, and supporter. Michael E. Porter has developed three strategic focus, that is: (1) competitive advantage: cost differentiation, focus, innovation, alliance, growth, quality; (2) value chain model, and (3) competitive forces model. Information technology is strategic if it supports one or more competition strategic. Companies are facing threats and opportunities from the outside. Threats are coming from new competitors, product/service substitute, consumer’s bargaining power and present competitors. The application of information strategic (IS) to get strategic advantages isn’t always easy. Companies should consider factors which may influence the failure or success of strategic information strategic (IS) application. Since it is important, managers need to carefully identify any information technology opportunity in order to give their companies benefit.Keywords: information technology, information strategic, strategic focus, threats and opportunities.